Use of clinical quality indicators to improve lung cancer care in a regional/rural network of health services. (4th April 2019) - Kim, Michelle Lynne; Matheson, Leigh; Garrard, Brooke; Francis, Michael; Broad, Adam; Malone, James; Eastman, Peter; Rogers, Margaret; Yap, Cheng‐Hon
Abstract: Problem: Optimal lung cancer care requires multidisciplinary team input, with access to specialised diagnostic and therapeutic services that may be limited in rural or regional areas and impact clinical outcomes. Clinical quality indicators can be used to measure the quality of care delivered to patients with lung cancer in a region and identify areas for improvement. We describe the implementation of internationally recognised clinical quality indicators for lung cancer care in the Barwon South Western region. Design: The consensus of an expert panel was used for the selection of clinical quality indicators. The data were retrospectively collected from the Evaluation of Cancer Outcomes Barwon South West Registry, which systematically records detailed information on all new patients with cancer in the region. Setting: Region‐based health service. Key measures for improvement: Adherence to clinical quality indicator targets. Strategies for change: Clinical quality indicators, which fall short of the expected targets, highlight areas for improvement in the service provided to patients with lung cancer. These results have prompted changes in the service offered to these patients, such as the introduction of a multidisciplinary lung cancer clinic. Effects of change: The multidisciplinary lung cancer clinic has streamlined the access to lung cancer services, including specialist consultations, diagnostics and therapeutic services, in a regional setting. Ongoing data collection is required to determine the effect of such changes on adherence to clinical quality indicator targets. Lessons learnt: The regular monitoring of clinical quality indicators serves as a useful method of quality assurance in the care of patients with lung cancer. We expect these clinical quality indicators to also be used by other health services to analyse and improve services provided to patients with lung cancer.